Comparison Of The Robusta Coffee Trade Value Chain In The Pakel And Kenongo Village Farmer Groups, Gucialit Sub-District, Lumajang Regency - Firmansyah, Idham; Gunawan, Cakti Indra; Dyanasari (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2025)
This research aims to analyze the system and efficiency of robusta coffee trading systems in Pakel Village and Kenongo Village, Gucialit District, Lumajang Regency, with a focus on marketing channels from farmers to consumers. The methods used include descriptive analysis, marketing margin and SWOT, with 64 respondents taken through proportional random sampling. The research results show that Pakel Village has 4 marketing channels with a production of 277 kg, while Kenongo Village has 5 channels with a production of 410 kg. The level of marketing efficiency in both villages is optimal, with a K/B ratio (>1) in each marketing institution. Development strategies show the dominance of strengths and opportunities over weaknesses and threats. It was concluded that marketing of robusta coffee in both villages was efficient, but marketing strategies needed to be improved through strengthening farmer institutions and diversifying marketing channels